Plutonium chlorido nitrato complexes: ligand competition and computational metrics for assembly and bonding. Issue 85 (8th October 2018) - Surbella, Robert G.; Ducati, Lucas C.; Autschbach, Jochen; Pellegrini, Kristi L.; McNamara, Bruce K.; Schwantes, Jon M.; Cahill, Christopher L.
Abstract : Four novel Pu(iv ) nitrato chloro complexes were crystallographically characterized and the Pu–ligand bond nature was delineated computationally. Abstract : Four new [Pu(iv )Cl n (NO3 )6− n ] 2− ( n = 0, 2, 3) and [Pu(vi )O2 Cl3 (NO3 )] 2− containing materials were crystallized from acidic, aqueous media and structurally characterized. The anions are assembled via hydrogen and halogen bonding motifs, which are rationalized computationally. The Pu–NO3 and –Cl bonds were probed using QTAIM and NLMO analyses and found to be polar and largely ionic.